(1)当n为偶数,即n=2k,(k∈Z)时,
f(x)=
cos 2 (2kπ+x)• sin 2 (2kπ-x)
cos 2 [(2×2k+1)π-x] =
cos 2 x• sin 2 (-x)
cos 2 (π-x) =
cos 2 x• (-sinx) 2
(-cosx) 2 =sin 2x,(n∈Z)
当n为奇数,即n=2k+1,(k∈Z)时f(x)=
cos 2 [(2k+1)π+x]• sin 2 [(2k+1)π-x]
cos 2 {[2×(2k+1)+1]π-x} =
cos 2 [2kπ+(π+x)]• sin 2 [2kπ+(π-x)]
cos 2 [2×(2k+1)π+(π-x)] =
cos 2 (π+x)• sin 2 (π-x)
cos 2 (π-x) =
(-cosx) 2 • sin 2 x
(-cosx) 2 =si n 2 x,(n∈Z)
∴f(x)=sin 2x;
(2)由(1)得 f(
π
2010 )+f(
502π
1005 )=si n 2
π
2010 +si n 2
1004π
2010
= si n 2
π
2010 +si n 2 (
π
2 -
π
2010 ) = si n 2
π
2010 +co s 2 (
π
2010 )=1